Use of the Global Burden of Disease methodology to estimate disease burden of air pollution in England. (November 2016) - Schmidt, Jürgen C; Hughes, Andrew; Fox, Sebastian
Abstract: Background: An analysis of data from the Global Burden of Disease (GBD) Study 2013 highlighted the role of air pollution and the concomitant lack of published data linking this risk with fatal and non-fatal outcomes. The GBD methodology improves comprehensively estimation of the health outcomes attributable to air pollution, broken down by geography and socioeconomic deprivation. The aim of our study was to assess the suitability of GBD model estimates to provide a comprehensive overview of air pollution. Methods: The GBD methodology divides risk factors into three main categories—behavioural, metabolic, and environmental, the latter including air pollution. Data and methods from the GBD 2013 study were used to relate air pollution (annual average daily exposure to outdoor air concentrations of particulate matter) to the burden of disease, in particular disability-adjusted life-years (DALYs), in England between 1990 and 2013. The analysis distinguished between English regions, and between subregional areas divided into quintiles by the Index of Multiple Deprivation score. Findings: Between 1990 and 2013, the rates of DALYs attributed to each of the three major risk categories have declined, as has the exposure to tobacco, high blood pressure, cholesterol, and air pollution. Among leading risk factors, air pollution has moved from rank nine in 1990 to rank 12 in 2013, responsible for 294 DALYs per 100 000 (age-standardised, both sexes). Environmental risks still cause 4·7% (648 099) of total DALYs. A substantial and consistent gap continues to exist between most and least deprived quintiles of the population, and most and least deprived regions. In 1990 the poorest people in North West England lost 1415·5 years of life compared with 656·4 lost by the richest people in South East England. The data for 2013 were 477·2 and 188·9, respectively. Interpretation: The importance of air pollution as a risk factor in England has decreased over the past 20 years but remains quantitatively important. There is a consistent gap across time between regions and levels of deprivation. The GBD programme offers a comprehensive methodology to monitor evolution over time and across regions. Funding: Public Health England.